Islamic identity in Kazakhstani society: cultural contexts of historical continuity (Eurasian Journal of Religious Studies, 2025)
The present article examines the importance of Islamic identity as one of the elements determining the development of public consciousness and the formation of the image of the future of Kazakhstani society. The article aims to study the axiological content of Islamic identity for its influence on the formation of views and values ​​in modern Kazakhstani society. The scientific significance of the work lies in updating the features of the formation of Islamic identity in the context of the Turkic cultural and communicative space, the historical and cultural context of the Islamic revival in the country, as well as the characteristics of the discourse of de-Westernization emerging in Islamic intellectualism. The practical significance of developing a viable model of Islamic identity in Kazakhstani society is explained by the importance of the research results for the development of domestic humanitarian discourse, as well as for the development of the concept of spiritual security. The study applied general philosophical methods, as well as the method of historical reconstruction. The authors conclude that the historically and culturally conditioned syncretic nature of the Kazakhstani model of Islamic identity meets the needs of tolerant coexistence of diverse ethnoconfessional groups in the country. The key findings of the study also include an understanding of Kazakhstan's Islamic identity as a combination of Islam's spiritual role and its political neutrality, which is conditioned by the secular and multiethnic nature of society. The study's value lies in the development of a number of practical recommendations regarding the role of Islam in strengthening ethnic and religious harmony, social cohesion, societal consolidation, and the preservation of cultural diversity, which constitutes the practical significance of the findings.Keywords: Islamic identity in Kazakhstan, Islamic revival, Sufism in Kazakhstan, vision of future society, theory of de-Westernization.